The Mitford affair : [large type] a novel - Benedict, Marie (Thorndike Press large print core series., 2023)
"Between the World Wars, the Mitford sisters dominate the English political, literary, and social scenes. Though they've weathered scandals before, the family falls into disarray when Diana divorces her wealthy husband to marry a fascist leader and Unity follows her sister's lead all the way to Munich, inciting rumors that she's become Hitler's mistress. As the Nazis rise in power, novelist Nancy Mitford grows suspicious of her sisters' constant visits to Germany and the high-ranking fascist company they keep. When she overhears alarming conversations and uncovers disquieting documents, Nancy must make excruciating choices as Great Britain goes to war with Germany"--